2006
DOI: 10.1021/jp063459+
|View full text |Cite
|
Sign up to set email alerts
|

Size-Manipulable Synthesis of Single-Crystalline BaMnO3 and BaTi1/2Mn1/2O3 Nanorods/Nanowires

Abstract: We report a size-manipulable synthesis of single-crystalline nanorods/nanowires of barium manganite (BaMnO 3 ) and barium titanium manganite (BaTi 1/2 Mn 1/2 O 3 ) by using the composite-hydroxide-mediated approach. The synthesis cleanly yields nanorods with a hexagonal perovskite structure. Typical nanorods have widths ranging between 50 and 100 nm, and the lengths can be easily controlled by time and temperature or by adding a small amount of water during the synthesis process. Resistance measurement shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Liu et al 41 have demonstrated a generic approach for the synthesis of single -crystal complex oxide nanostructures of perovskites, spinels, and various hydroxides, including monoclinic, corundum, CaF 2 -struc tured, tetragonal, and metal hydroxides. 42,43 The method is based on a reaction between a metallic salt and a metallic oxide in a solution of composite hydroxide eutectic at ϳ200ЊC and 1 atm without using an organic dispersant or capping agent. This one -step synthesis technique is cost -effective, easy to control, and can be conducted at low temperature and normal atmospheric pressure.…”
Section: Nanowires Of Functional and Smart Materialsmentioning
confidence: 99%
“…Liu et al 41 have demonstrated a generic approach for the synthesis of single -crystal complex oxide nanostructures of perovskites, spinels, and various hydroxides, including monoclinic, corundum, CaF 2 -struc tured, tetragonal, and metal hydroxides. 42,43 The method is based on a reaction between a metallic salt and a metallic oxide in a solution of composite hydroxide eutectic at ϳ200ЊC and 1 atm without using an organic dispersant or capping agent. This one -step synthesis technique is cost -effective, easy to control, and can be conducted at low temperature and normal atmospheric pressure.…”
Section: Nanowires Of Functional and Smart Materialsmentioning
confidence: 99%
“…The Ba-doped CeO 2 is synthesized through the newly invented nanomaterial fabrication route of the CHM method [11][12][13][14][15]. In a typical reaction, a 9 g amount of mixed NaOH and KOH with a Na/K ratio of 51.5:48.5 is placed in a 25 ml covered Teflon vessel.…”
Section: Methodsmentioning
confidence: 99%
“…Normally carrier localization at the grain boundary changes the conductivity to semiconducting or insulating and carrier delocalization leads to metal like behaviour.The hopping is characterized by the parameter T 0 which is related to electronic density of states N(E f ) and radius of localization length(a) by T o = 18/k B N(E F )a 3 . High T 0 value indicates multiphonon hopping with a large increase in the localization length and increase in barrier height at the grain boundaries leads to insulating and if T 0 decreases, based on hopping range and energy, the material remains in the metallic state of mott's transition [8,19]. Size of the grain and width of grain boundary inthe order of ρ ρ nanometers (or the localization length 'a' (1/ )) will correspond to 100% spin polarization by tunneling mechanism [28,29].…”
Section: Variable Range Hopping Mechanism (Vrh)mentioning
confidence: 99%
“…Sb 2 O 3 during the synthesis acts not only as reactant but also as an additive for decreasing the reaction temperature for phase formation from 1200 0 C to 900 0 C. The decreased reaction temperature for phase formation is due to the change in the eutectic point [8] of the mixture of all the reactants since additives provide liquid -phase grain growth at low temperature [9,10]. Thus the synthesis at a temperature less than the eutectic temperature of a mixture enhances the phase formation and control of particle size [11].High reaction temperature for phase formation, nonhomogeneous mixing and agglomeration are commonly found in synthesis of oxide materials by solid state reaction [12].…”
Section: Introductionmentioning
confidence: 99%